Efeito de um formulado desenvolvido com guaraná e semente de açaí em modelos experimentais pós-cirúrgicos: estudo da reparação in vitro e in vivo - Felin, Fellipe Danezi (2021)
Introduction: Tissue repair is a complex process that requires activation of mediators and mechanisms related to healing and regeneration. Healing involves inflammation, fibroblast proliferation and collagen remodeling. Studies have elucidated the modulation of repair at the molecular and biochemical level in an attempt to avoid pathological scarring. The repair can be influenced by the patient's nutritional status and, therefore, be stimulated by products originating from plants, including guarana and açaí, which have a healing effect by modulating the inflammatory and proliferative phases. It is possible that the combination of these results in a potential innovative pharmacological product, with high healing power. Objective: To evaluate the effect of the formula, developed with guarana and açaí seeds, in an experimental model of post-surgical repair, in vitro and in vivo. Methods: The study does not need to be approved by the Ethics Committee. Initially, the conjugate extract Guaraná-Açai (GA) was developed using hot water and citric acid, the extract was obtained and the chemical analysis was carried out through mass spectrophotometry. The antioxidant and genoprotective capacity of GA were analyzed respectively by the DPPH and Gemo tests. A pharmacological concentration-response curve (1, 3, 5, 10 and 30 μg / mL) in fibroblasts (HFF-1) and keratinocytes (HaCAT) both commercially obtained was performed and the concentration of choice for the other tests was 5 μg / mL. In fibroblasts, the strach assay was performed, the so-called in vitro wound assay, after 3,6, 24 and 72 hours of injury induction and treatment, oxidative markers were analyzed, apoptotic marker after 24 hours, total collagen after 24, 48 and 72 hours and analysis of the expression of genes related to proliferation, collagen and inflammation after 24 hours. A second in vivo protocol was performed using Eisenia fetida earthworm after 1,3,6,12 and 24 hours of the surgical caudal incision between the third and fifth posterior segment, and addition of treatment with GA or phosphate buffer for the control animals, macroscopic and histological analysis was performed using Masson staining -Goldner.The SOX-4 gene was measured via RT-PCR after 3 and 24 hours. Results: Sixteen bioactive molecules, including some substances never previously described in the isolated extracts, were identified. All concentrations tested in the cell model exhibited non-cytotoxic and antioxidant effects in addition to genoprotective. The concentration of choice 5 μg / mL showed pro-regeneration effects in an in vitro model. The GA extract accelerated the healing processes observed in cells and through macroscopic and histological analysis in earthworms. Conclusion: Despite the methodological limitations, these results indicated that the GA extract has the potential to accelerate the healing/regeneration of wounds induced in vitro or surgically in vivo. More studies need to be carried out so that these results can become a product to be made available to the population, bringing benefits to society as a whole.